Study of structure and fatigue strength of thermoplastic elastomers modified with nanoparticles and radiation-crosslinked - Rybko, M.; El Fray, M. (Polimery, 2014)
This paper describes the synthesis of semicrystalline poly(aliphatic/aromatic-ester)s (PED), their modification and evaluation of thermal and mechanical properties, including fatigue resistance. PED multiblock elastomers are composed from hard segments [as in poly(butylene terephthalate) (PBT)] and butylene esters of dilinoleic fatty acid (DLA) forming the soft segments. PED copolymers were modified with nanoscale particles of SiO2 introduced during the synthesis at variable concentrations (0.2, 0.5 and 1.0 wt %), and were further irradiated by high energy electron beam with doses of 25, 50 and 75 kGy. The chemical structure of PED copolymers was determined using ATR FT-IR and 1H NMR spectroscopy. Phase structure of the materials modified by nanoparticles and e-beam was determined from DSC, TEM and gel content analyses. The mechanical properties were determined from the quasi-static tensile strength and Young's modulus values as well as dynamic short and long term fatigue tests, abbreviated as SILT and SLT method, respectively. The results, analysed in terms of the effect of nanoparticles content and radiation dose on selected properties of the obtained materials, indicate that the applied modification methods allow to improve fatigue resistance (a significant reduction of absolute creep) by a synergy between the processes occurring during the modification of PED copolymers with nanoparticles and ionizing radiation. Fatigue properties are important for future applications of PED as implants subjected to long term cyclic deformations.